The work of the dead a cultural history of mortal remains - Laqueur, Thomas Walter 1945- (Princeton University Press, 2015)
Cover -- Title -- Copyright -- CONTENTS -- Preface -- Acknowledgments -- Introduction: The Work of the Dead -- PART I THE DEEP TIME OF THE DEAD -- 1 Do the Dead Matter? -- 2 The Dead Body and the Persistence of Being -- 3 The Cultural Work of the Dead -- PART II PLACES OF THE DEAD -- 4 The Churchyard and the Old Regime -- The Development of the Churchyard -- Language -- Place -- The Church and Churchyard in the Landscape -- Necrogeography -- Necrobotany -- Necrotopology and Memory -- The Life and Afterlife of the Churchyard in Literature -- The Passage of the Dead to the Churchyard -- Law -- Exclusion from the Churchyard -- The Claims of the Dead Body on the Parish Churchyard -- The Claims of the Parish on the Dead Body -- The Economics of Churchyard Burial -- The Right to Burial and the Crisis of the Old Regime -- Enlightenment Scandals -- Voltaire -- David Hume -- 5 The Cemetery and the New Regime -- The Danger of the Dead and the Rise of the Cemetery -- Genealogies of the New Regime -- Imagination: Elysium, Arcadia, and the Dead of the Eighteenth Century -- Cimetière du Père- Lachaise -- Distant Lands and the Imperial Imagination -- The Age of the Cemetery -- Novelty -- Necrogeography and Necrobotany -- Cemeteries and Capitalism -- Religious Pluralism in the Age of the Cemetery -- Reform, Revolution, and the Cemetery -- Class, Family, and the Cemetery -- Putting the Dead in Their Place: Pauper Funerals and Proper Funerals, Burials and Reburials -- Disrupted Bodies -- PART III NAMES OF THE DEAD -- 6 The Names of the Dead in Deep Time -- Names of the Dead in Times of War -- Names of the Dead in Times of Peace -- 7 The Rise of the Names of the Dead in Modern History -- 8 The Age of Necronominalism -- Names over Bodies -- Names and the Absent but Present Body -- Monumental Names -- Names of the Vanished Dead -- 9 The Names of the Great War.